2012
DOI: 10.4300/jgme-d-11-00154.1
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Comprehensive In-Training Examination Course Can Improve Residency-Wide Scores

Abstract: A multifaceted residency-wide examination curriculum focused around an intensive 14-week course was associated with marked improvement on the in-training examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Individual education plans suggest good results in remediating residents at risk of failing the board exam. 26,27 Intensive, multimodal approaches for remediation of surgery, 28 emergency medicine, 29 and radiology 30 residents have been shown to improve board scores. The universal finding among these studies was that intervention was costly, 31 with one report suggesting that better methods of identifying residents at risk would help to screen residency candidates.…”
Section: Discussionmentioning
confidence: 98%
“…Individual education plans suggest good results in remediating residents at risk of failing the board exam. 26,27 Intensive, multimodal approaches for remediation of surgery, 28 emergency medicine, 29 and radiology 30 residents have been shown to improve board scores. The universal finding among these studies was that intervention was costly, 31 with one report suggesting that better methods of identifying residents at risk would help to screen residency candidates.…”
Section: Discussionmentioning
confidence: 98%
“…It was anticipated that a GSSE short course would improve participants’ success in passing the GSSE, although there are few published studies on the success of courses with similar objectives . We report a prospective qualitative evaluation of its effectiveness undertaken during the first year of the course.…”
mentioning
confidence: 99%
“…The most frequently used strategy is adding a course to prepare trainees for the in-training or board-certifying examination. These courses have been shown to improve ITE scores, [10][11][12][13][14][15] although not universally, particularly with shorter courses. 16,17 Peer-led courses or study groups have been shown to work in neurology, 18 but have had mixed results in a psychiatry 19,20 program.…”
Section: Introductionmentioning
confidence: 99%